Illustrations in Biographical Studies: Sharing Experience of Preparing The Chronicle of Life and Work of Sergey Esenin - Maksim V. Skorokhodov (Studia Litterarum)
The article discusses the function of illustrations in biographical studies. In particular, it examines a section “Appendix” in the 5-volume Chronicle of Life and Work of Sergey Esenin that includes documentary and visual materials. The use of illustrations not only makes a biographical study attractive to readers, but also serves as a welcome supplement to the information contained in the main part of the chronicle.